VD_FINDINFO HC / 2013 / 799 vom 9. Dezember 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, OBSERVATION DU DÉLAI, DÉLAI DE RECOURS | 138 al. 3 let. a CPC (CH), 321 al. 2 CPC (CH), 337 CPC (CH), 339 al. 2 CPC (CH)